The control of differential tectonics on the formation of deep reservoirs in lacustrine rift basins: An insight of the Bodong Low Uplift in the Bohai Bay Basin, East China - Qunfeng Ding; Yuhang Chen; Lei Chen; Lei Gao; Shaofeng Bu; Yuxing Liu; Dongye Ma; Rongjun Zhang; Lijun Song; Le Qu (Energy Geoscience)
Tectonic activities significantly impact deep reservoir properties via sedimentary and diagenetic processes, and this is particularly true for lacustrine rift basins. The tectonic-sedimentary-diagenetic-reservoir system is crucial in deep reservoir exploration. This study examined the first member and upper submember of the second member of the Dongying Formation in the Bodong Low Uplift in the Bohai Bay Basin (East China), documenting the petrologic features and physical properties of reservoirs in different tectonic sub-units through integrated analysis of log and rock data, along with core observation. A mechanism for deep reservoir formation in lacustrine rift basins was developed to elucidate the sedimentary and diagenetic processes in complex tectonic settings. The results show that tectonic activities result in the occurrence of provenances in multiple directions and the existence of reservoirs at varying burial depths, as well as the significant diversity in sedimentary and diagenetic processes. The grain sizes of the sandstones, influenced by transport pathways rather than the topography of the sedimentary area, exhibit spatial complexity due to tectonic frameworks, which determine the initial pore content of reservoirs. However, the burial depth, influenced by subsequent tectonic subsidence, significantly impacts pore evolution during diagenesis. Based on the significant differences of reservoirs in slope zone, low uplift and depression zone, we establish different tectonic-diagenetic models in deep complex tectonic units of lacustrine rift basins.